Langkah Kolaboratif Guru dalam Manajemen dan Intervensi Pembelajaran Model Pull Out bagi Siswa Slow Learner - Fajar Fithroni; Wiwit Ika Setiyati; Abdurrahman Abdurrahman; Wahid Aditiono; Raphael Krismanto Priyoatmojo (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Learning for slow-learners requires more specialized management and intervention than general students. Collaborative steps must be taken with teachers and parents to obtain comprehensive data and processes for the progress of slow-learner students. This best practice aims to: 1) Provide a realistic depiction of slow-learner students, especially in mathematics, 2) Present a report on the learning management process to the intervention given to slow-learner students in mathematics, and 3) Provide an overview of the collaboration of stakeholders at SMP Negeri 12 Yogyakarta. The subjects were grade VII slow-learner students in semester 2 of the 2023/2024 academic year. The research method was qualitative descriptive. In general, learning management and interventions implemented by Special Guidance Teachers (GPK) and other teachers for slow-learners at SMP Negeri 12 Yogyakarta have been carried out in a structured manner. It requires the collaboration of various school stakeholders. The establishment of collaboration between GPK and school principals, subject teachers, parents, and BK teachers from the assessment to follow-up planning is a very positive collaborative step, developed gradually through task-oriented and person-oriented interpersonal communication. However, there are still communication constraints and time that still need to be evaluated and improved as a follow-up step for better intervention.